The Influence of Leadership and Work Conflict on Employee Performance at PT. PLN ULPLTD Galala Ambon”. - Hiariey, Harvey; Tehuayo, Erlinda; Duwila, Ummi; Matdoan, Arsad; Serang, Mohamad R. (Jurnal Ekonomi, 2024)
Leadership plays an important role in the company for the achievement of organizational progress, a good leader will direct his subordinates in carrying out the tasks and responsibilities given. while work conflict is a conflict between two or more members of individuals with activities together in different goals, status, values ​​and different perceptions. This study aims to determine:1). The influence of leadership on employee performance of PT. PLN ULPLTD Galala Ambon 2). The Effect of Work Conflict on Employee Performance at PT. PLN ULPLTD Galal Ambon. The method used is a quantitative research method. the sample in this study were 35 respondents. Data collection techniques in this study consisted of observations, interviews and questionnaires that have been tested for results. Based on the results of the study it can be concluded that 1). Leadership has a significant effect on employee performance as seen from the results of regression analysis showing Leadership has a Tcount of 0.513 with a significance of 0.001 (significant). 2). Work conflict has a significant effect on employee performance as seen from the results of regression analysis showing work conflict has a Tcount of 0.911 with a significance of 0.000 (significant).